Penerapan IT Governance untuk Meningkatkan Efektivitas dan Akurasi Pencatatan Santunan Kematian di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Klungkung - Yoga Pramana, Ida Bagus Gde; Indriyani, Indriyani (Universitas Komputer Indonesia, 2025)
The Civil Registration Office (Disdukcapil) is a government agency responsible for managing population administration and civil registration in Indonesia. The main task of Disdukcapil is to ensure accurate and up-to-date population data, and to provide services related to population documents to citizens. As a Regional Apparatus Organization that is in very close contact with all levels of society, of course Disdukcapil is expected to provide services by prioritizing 3S, namely Smile, Greeting and Greeting. Improving the quality of services that have now switched to using the system certainly makes it very easy for Disdukcapil Operators to operate the system. The people who come will easily be served with all kinds of needs. One of the community needs that is very often taken care of at Disdukcapil is the processing of Death Certificates. One of the important requirements in obtaining a death certificate is to attach a Death Certificate issued by the Hospital or Lurah / Village Office. As one of the innovations of service to the community, Klungkung Regency Disdukcapil rewards the processing of Death Certificates to Heirs by providing Death Compensation. However, with the positive enthusiasm of the Klungkung Regency community, it is certainly necessary to implement IT Governance using the COBIT 5 framework as governance to increase the effectiveness and accuracy of death registration.